Long-term outcomes of anti-VEGF treatment with 5+PRN regimen for macular edema due to central retinal vein occlusion - Ya Ye; Yu-Meng Deng; Zhen Huang; Qiao-Wei Wu; Yan-Nian Hui; Yan-Ping Song (International Journal of Ophthalmology, 2023)
AIM: To assess the long-term outcomes of treating macular edema (ME) associated with central retinal vein occlusion (CRVO) with a regimen of “5+pro re nata (PRN)”. METHODS: This retrospective study included 27 eyes of 27 patients with ME associated with non-ischemic CRVO (non-iCRVO group, n=15) and ischemic CRVO (iCRVO group, n=12). The eyes were treated with five consecutive intravitreal injections of conbercept or ranibizumab, followed by reinjections as needed or PRN. Retinal laser photocoagulation or intravitreal dexamethasone implants (DEX) were implemented in both groups when necessary. The best-corrected visual acuity (BCVA, logMAR) and central retinal thickness (CRT) were recorded at baseline, at 1, 2, 3, 4, 5, 6, and 12mo, and at the final visit. The efficacy rates of BCVA and CRT before and after treatment were calculated. The number of injections at each visit and the incidence of adverse events were also recorded. RESULTS: The patients, aged 59.4±15.1y, were followed up for 24.7±8.8mo (range: 15-42mo). After treatment, BCVA improved significantly from 1.04±0.56 logMAR at baseline to 0.59±0.36 logMAR (P=0.038) at the final visit in all patients. Both the non-iCRVO and the iCRVO groups achieved improved BCVA compared to the baseline at all visit points, but there was no statistical significance (P=0.197 and 0.33, respectively). The mean CRT was statistically reduced compared to baseline at all visit points in all the eyes and in both groups (all P<0.001). The apparent effective rate was 22.22% for BCVA and 37.04% for CRT after the first injection, 48.15% for BCVA and 62.96% for CRT after 5 consecutive injections, and 74.08% for BCVA and 100% for CRT at the end of follow up. The average number of injections in all patients was 9.0±2.4 at 12mo and 14.9±8.1 finally with no statistical significance between both groups (P>0.05). Laser treatment was applied to all eyes in the iCRVO group, while only 5 patients in the non-iCRVO group. Six patients in the non-iCRVO group and 3 patients in the iCRVO group had a drug switch. DEX was applied to 4 eyes in the non-iCRVO group and 5 eyes in the iCRVO group. CONCLUSION: The 5+PRN anti-vascular endothelial growth factor (VEGF) regimen is found to be safe and effective for both iCRVO and non-iCRVO, especially in the iCRVO group. The best regimen for such patients needs to be further investigated. Adjuvant laser therapy and DEX are necessary in some cases.